When Canons Can Corrupt: Clear Statement Rules in Administrative Law - McGarity, Thomas (Columbia Journal of Environmental Law, 2025)
Administrative law is emerging as a major focus of the Roberts Court’s efforts to reshape American society. And the primary vehicle for the Court’s transformation of administrative law is the clear statement rule, which provides that federal agencies must point to clear language in their enabling statutes when they address issues that trigger the clear statement rules. In administrative law, those issues include federalism, major questions, and property rights. The demise of the Chevron doctrine is unlikely to disturb this trend, because the normative clear statement rules examined in this article go beyond nondeference to agency statutory interpretation to limit Congress’ power to enact statutes containing broad language empowering agencies to adapt to changing circumstances. This article explores the virtues and disadvantages of aggressive judicial deployment of clear statement rules and concludes that the considerable disadvantages outweigh the modest virtues. The clear statement rules have no textual basis in the Constitution or statute. They are instead built on norms that are putatively located somewhere in the Constitution, but in fact are mirages that appear concrete from a distance, yet disintegrate on close inspection. They are therefore easily manipulable to achieve policy outcomes preferred by the judges applying them. At the same time, they unjustifiably limit Congress’ power to use broad language in statutes to allow implementing agencies to adapt to changing conditions, technological advances, and attempts by regulated entities to circumvent implementing regulations. Furthermore, the high bar for clarity that the Supreme Court has established and the vanishingly small likelihood that Congress will react to a judicial remand with legislation specifically empowering the agency to take the judicially rejected action ensures that clear statement rules are in reality weapons in a broader assault on the administrative state. As such, they are undermining the legitimacy of judicial review. The article briefly probes possible responses to the judicial aggrandizement represented by clear statement rules in administrative law. Among other things, Congress could amend the Administrative Procedure Act to prescribe a standard for judicial review of agency statutory interpretation that precludes judicial use of clear statement rules. Because it is highly unlikely that proponents of protective federal regulation will persuade Congress to act in an era of extreme political polarization, however, the article concludes that the best way for the Court to restore the legitimacy of judicial review is to approach the task of statutory interpretation with greater humility and less enthusiasm for advancing a libertarian agenda.